2021
DOI: 10.1007/s40619-021-00955-9
|View full text |Cite
|
Sign up to set email alerts
|

La Non-Alcoholic Fatty Liver Disease, una patologia epatica di interesse endocrinologico

Abstract: SommarioLa Non-Alcoholic Fatty Liver Disease (NAFLD) comprende diversi stadi di patologia epatica che vanno dalla steatosi alla cirrosi epatica. È considerata la manifestazione epatica della patologia metabolica e alcune alterazioni endocrinologiche possono concorrere a determinarne l’insorgenza o la progressione. È quindi di fondamentale importanza che l’endocrinologo sia consapevole dell’importanza clinica e prognostica della NAFLD correlata alle patologie endocrine, al fine di offrire al paziente il trattam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, GH is typically elevated at the onset of sleep, with the highest levels during SWS and starts to decline during the fourth decade of life [158]. Growth hormone deficiency has been linked with an increase in fat accumulation in adults [159,160], and some studies reported an increase in hepatic steatosis, even though the results are not univocal [161].…”
Section: Key Molecules Linking Metabolism and Sleep In Animals And Hu...mentioning
confidence: 99%
“…On the other hand, GH is typically elevated at the onset of sleep, with the highest levels during SWS and starts to decline during the fourth decade of life [158]. Growth hormone deficiency has been linked with an increase in fat accumulation in adults [159,160], and some studies reported an increase in hepatic steatosis, even though the results are not univocal [161].…”
Section: Key Molecules Linking Metabolism and Sleep In Animals And Hu...mentioning
confidence: 99%
“…Metabolic disturbances, included diabetes and non-alcoholic liver disease, are strictly connected among each other, and they similarly interact with lack of sleep. Metabolic disturbances are often associated to hormonal imbalances, which may play a role in their development, in a complex relationship of mutual influence (33)(34)(35)(36). Some hormones may be involved in the association between metabolic disturbances and reduced sleep.…”
Section: Introduction 1sleep Disturbances and Metabolic Disturbances:...mentioning
confidence: 99%